PENGARUH PENGUMUMAN LAPORAN KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA - Idham Lakoni (Universitas Prof. Dr. Hazairin SH, 2018)
Financial reports are important for investors as decision makers to invest their capital in certain issuers, announcements of financial statements can be good news or bad news for investors, so that at the time the financial statements of investors will react to stock prices which can ultimately affect stock returns that will received. This study aims to see differences in stock returns before and after the financial statements are announced, and to see whether the announcement of financial statements affect stock returns on companies that go public on the Indonesia Stock Exchange. This research was conducted by looking at changes in the average return of shares before and after the financial statements were announced. By using the purposive sampling method, a sample of 10 companies were selected on the Indonesia Stock Exchange. The observation period is carried out for 15 days, which is 7 days before the announcement of the financial statements, when the financial statements are announced and 7 days after the announcement of financial statements as of December 31, 2008 and 2009. In 2008 at the beginning of the observation (stock returns tend to be negative towards the announcement date financial reports there is a positive change because the information received by investors is good news as they expected, whereas in 2009 the initial observation of stock returns tended to be positive changes towards the negative approached the announcement of financial statements and returned to positive again after the announcement of financial statements this is because the information obtained by investors is not as good as expected. From the results of the study it can be seen that the announcement of financial statements is considered good news by investors so that it has a positive effect on stock returns, using tables and graphs. see changes in stock returns before and after the financial statements are announced, that is, after the financial statements are announced, stock returns tend to increase more than before the financial statements were announced